Marine geology of Korean seas. - Chough, Sung Kwun, 1946- (Elsevier Science B.V., 2000)
Tremendous progress has been made in the geological understanding of the Korean seas with the advances in sophisticated exploration techniques, specifically in the areas of marine geophysics, sedimentology, geochemistry, and palaeoceanography, since Marine Geology of Korean Seas was first published in 1983. This book gives a comprehensive overview of the marine geology of these unique seas, including physiography, sedimentary facies and depositional processes of surface sediments, sequence stratigraphy, geologic structures, and basin evolution. In this edition, new results and interpretations have been incorporated that help to formulate geological models on the evolution of the Korean seas in relation to the adjacent continents.